Rethinking Professional Experience Through a Learning Community Model: Toward a Culture Change - Broadley, Tania; Martin, Romana; Curtis, Elizabeth (Frontiers in Education, 2019)
Preparing pre-service teachers to become effective future educators has become increasingly complex in an environment of rapid change, economic uncertainty, technological advancements and cultural diversity. Contemporary initial teacher education is evolving and adapting to the changing organisational environments and cultures in organisations who partner in equipping pre-service teachers to become knowledgeable, innovative and professional in their teaching and skilled in effectively connecting, interacting and collaborating in professional communities. Professional experience placements provide pre-service teachers with the opportunity to participate in teaching in real world settings guided by experienced teachers and supported by university supervisors; however, the diverse approaches to professional experience adopted by educational organisations, influence pre-service teachers’ experiences and outcomes. Cultural and socio-economic factors across different sites also impact on the outcomes of students’ professional experience due to variations in the organisational culture and settings. In this paper we explore the evolution of professional experience from traditional to contemporary, the role of the third space in professional experience, and the complexities in developing a unified approach in universities and early childhood sites/schools, organisations that have very different cultures yet are committed to developing effective teachers. We highlight the advantages of adopting a learning community model for professional experience in which mentoring is central to success. A theory-based model of professional experience, 3PEx, based on a learning community approach and the merging of cultures in professional experience and learning contexts, is introduced. This model is informed by the literature and results of a recent study of professional experience in a university reimagining initial teacher education to meet contemporary standards. The challenges of achieving cultural change in the professional experience arena are explored, and a range of strategies suggested that can lead to a deeper understanding of the cultural landscape and the needs of pre-service teachers in their transition to teaching.